Syariah-Compliant Fintech in Banking: Bridging Financial Gaps in Indonesia and the Philippines - Purnamasari, Rini; Rismala; Ibrahim, Hasmiene Diocolano (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2024)
Purpose – This study aims to explore the role of Sharia-compliant Fintech in addressing financial and cultural gaps in Indonesia and the Philippines Method – Utilizing a mixed-methods approach, the research integrates qualitative interviews and focus group discussions with quantitative surveys analyzed using Structural Equation Modeling (SEM) Findings – The findings reveal that Indonesia’s advanced regulatory framework and market maturity enable robust adoption of Sharia-compliant Fintech, enhancing financial inclusion for underserved communities. In contrast, the Philippines, particularly the BARMM region, demonstrates untapped potential hindered by limited infrastructure and regulatory gaps. Practical implications – Practical implications include the need for policymakers to develop comprehensive regulations, financial institutions to build trust, and technology innovators to design culturally aligned solutions Originality/value – comparative analysis of Sharia-compliant Fintech adoption in two socio-religiously distinct countries, providing actionable insights for scaling culturally sensitive financial technologies across Southeast Asia